The Revitalization of Yajé Shamanism among the Siona: Strategies of Survival in Historical Context. (September 2016) - Langdon, Esther Jean
Abstract: This article outlines the transformations of yajé shamanism among the Siona Indians of the Northwest Amazon Basin of Colombia. The shaman's role and the political and sacred use of yajé rituals have changed since colonial times and can be seen as a result of adaptive strategies for survival. This study examines the factors that have contributed to the current revitalization due to state and popular representations of the ecological and wise Indian. Although Gow and Taussig argue that ayahuasca shamanism in Peru and folk healing in Colombia rose out of colonial domination and proletarian concerns, Siona shamanic practices are best understood as a transfiguration and result of their particular response to outside forces. Their contemporary use of yajé reflects this past and the discourse, aesthetics, expectations, and demands of the larger society.